The sequence effect: Character position processing in Chinese words - Zhang, Yancui; Wang, Mengsi; Wang, Jingxin (Frontiers in Psychology, 2022)
Numerous studies indicate that letter position processing is important for word recognition; also, the position processing of external letters (especially the initial letter) is better than that of inner letters in the Roman script. Similarly, the position processing of characters is critical in Chinese word recognition. However, the position processing pattern of characters within Chinese words is still understudied. Therefore, using a single-presentation lexical decision task with 79 university students in China, we conducted two experiments with three- and four-character words to explore this issue. The results revealed clear character position processing with transposed pseudowords. Crucially, we identified a sequence effect in Chinese character position processing within words, directly supporting the hypothesis that character-based processing occurs with Chinese words. We also discussed other possibilities in Chinese character position processing.